Economic value added and market value added; can it be achieved by improving organisational capability at Debswana Diamond Company? - Pelaelo, Lemogang (My University, 2021)
The main objective of any organisation or business is to create wealth for its shareholders, and Debswana Diamond Company (Debswana) is not an exception. When revenue is more than the cost of doing business and the cost of capital, the business will create wealth for the shareholders. Therefore, wealth for shareholders can be defined as the present value of future returns expected from the equity invested. Maximising shareholders’wealth is important for all profit seeking organisations, regardless of the size of operations. The principle of increasing or maximising wealth is that, the objective of all the organisational activities should be about maximising value. It requires organisational management to have the ability to increase sales, earnings and free cash flow, which will possibly increase returns on funds invested in the business, while mitigating any associated risk of loss. Measuring an organisational value is important fororganisationsas measuring value takesinto account the interests of all stakeholders and not only shareholders. Stakeholders include shareholders, governments, citizensand anyone with interest to the organisation. Economic Value Added (EVA) is the internal measure of an organisational performance. Itis the difference between the current total market value of an organisation and the capital contributed by investors. It is a measure that is mostly associated with creation of wealth for shareholders over time. EVA an be increased through the actions and decisions of managers at the right time. Managers can make decisions and changes that create value using different continuous improvement methodologies. Organisationsthat use EVA as their financial performance measure focuson operational efficiency, which ensures that assets are closely managed. There are three tactics that can be used by organisations to increase EVA, either earn more profit without using more capital, by using less capital, and invest capital in high return projects. Market Value Added (MVA) is another measure that can be used to measure shareholders value. It is the difference between the organisational total market value and the capital invested.Itmeasures wealth and assesses the level of value that has been accumulated over a period of time by an organisationand is typically used for companies that are larger and publicly traded. EVA and MVA are considered criticalprincipleswhen evaluating an organisationalperformance with regard to measuring shareholders returns. They are financial performance indicators that can be used to measure the financial results and be correlated to the shareholders’ value creation. Thesetwo performance indicatorsmeasurethe true economic performance of an organisation. They are alsovitalto strategy formulations for the creation of shareholders’wealthby an organisation.Both the EVA and MVA are indicators of, and influenced by the capital invested; therefore any change in the capital invested influences the two indicators. There is therefore a need to develop Organisational Capability, especially when operating in a rapidly changing and highly turbulent environment like the mining industry. This can allow flexibility in decision making and agility to adapt to the international markets. Thisstudy is aiming at showing the importance of improving Organisational Capability by using the business improvement methodologies like the lean management. The 20 keys to organisationalimprovement is one of the tools that can be used for leanmanagement approach. This studyanalysedthe impactof implementation of the 20 keys to organisational improvement at one of Debswana’soperation (Orapa Letlhakane and Damtshaa mines). Debswana has shown benefits in improving its Organisational Capability through the 20 Keys to Workplace Improvement,even though doneat operational level. There were costs saved, improved efficiency and improved safety performance. Some of the benefits included improved morale of the teams, improvement of team works and accountability and ownership by employees
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Science in Engineering, 2021